2000
DOI: 10.1094/pdis.2000.84.5.593c
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Verticillium Wilt of Sugar Beet, Caused by Verticillium dahliae, in Greece

Abstract: Wilting sugar beet plants (Beta vulgaris L.) were observed in fields in the Larissa area of central Greece during the summers of 1997 and 1998. Diseased plants, showing general yellowing and epinasty, were sporadically distributed in the fields. As symptoms progressed, the outer leaves wilted and became desiccated. Inner leaves showed marginal and interveinal yellowing. These areas later turned brown and became necrotic. Longitudinal sections of the roots of diseased plants displayed browning of vascular tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…causing Alternaria leaf spot (McFarlane et al 1954), known seedborne pathogen P. betae causing Phoma leaf spot and root rot (Vaghefi et al 2019), Stemphylium spp. causing Yellow leaf spot (Hanse et al 2015) and Verticillium dahliae causing Verticillium wilt (Karadimos et al 2000). In the present study, we identified viable Alternaria spp.…”
Section: Discussionmentioning
confidence: 51%
“…causing Alternaria leaf spot (McFarlane et al 1954), known seedborne pathogen P. betae causing Phoma leaf spot and root rot (Vaghefi et al 2019), Stemphylium spp. causing Yellow leaf spot (Hanse et al 2015) and Verticillium dahliae causing Verticillium wilt (Karadimos et al 2000). In the present study, we identified viable Alternaria spp.…”
Section: Discussionmentioning
confidence: 51%
“…On sugar beet, the disease was initially attributed to Verticillium albo-atrum Reinke & Berthier insuggest Verticillium dahliae Kleb. is the causal agent (Puhalla 1979;Strausbaugh et al 1992;Karadimos et al 2000;Strausbaugh & Camp 2007a, 2007b, 2007cBrantner et al 2008;Harveson 2009). However, the causal agents may have been the same in all the studies, since Verticillium comprises a complex taxonomic group, which can lead to confusion over species identification (Inderbitzin & Subbarao 2014).…”
Section: Introductionmentioning
confidence: 99%